Majority and Token Minority Group Relationships: Power Acquisition and Communication - Fairhurst, Gail Theus; Snavely, B. Kay (Academy of Management Review, 1983)
Kanter's theory of numerical imbalance states that the successful integration of an organizational member whose social category (e.g.. sex. race) is different from the workgroup majority is an inverse function of the degree of imbalance in the numerical proportion of majority to minority members. This paper challenges this stand, arguing that individual responses to the token minority role and the majority member's role can vary when other sources of status and power are considered.